Minimum quality standards and compulsory labeling: More than the sum of its parts - Laura Birg; Jan S. Voßwinkel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper studies the effect of a minimum quality standard, a compulsory labeling scheme, and the combination of both instruments in a vertical differentiation model when not all quality dimensions of products can be observed byconsumers. Both a minimum quality standard on the non-observable quality dimension and a labeling scheme that informs consumers about the non-observable quality dimension have no impact on the observable quality dimension, increase prices, and have no impact on demand. The combination of a minimum standard and a labeling scheme increases prices, reduces or enhances investment in the observable quality dimension, and alters market shares depending on the minimum quality level. Compared to the case of no regulation, social welfare may decrease or increase under the minimum quality standard, the compulsory labeling scheme or the combined scheme, depending on the level of the minimum quality standard and the market size.
Keywords: L13; L15; L51; 330; minimum quality standards; labeling; vertical differentiation